Antioxidant protection of low density lipoprotein by procyanidins: structure/activity relationships - Porto, Patrícia Andréia Leite da Silva (2003)
The antioxidant activity of catechins and oligomeric procyanidins against low density lipoproteins peroxidation was studied by means of three distinct methods: cis-parinaric acid fluorescence decay, conjugated-dienes detection, and oxygen consumption. A relationship between the radical trapping efficiency of procyanidins and their structure was investigated. The results indicated that: (i) interflavan linkage type (C4---C6 or C4---C8) exerts a significant effect upon radical-trapping antioxidant activity of procyanidins. It is suggested that the conformation adopted by each procyanidin in aqueous solution influence their hydrophilic character, hence affecting their interaction with the peroxyl radicals present in aqueous phase and those in LDL particle (lipidic nature); (ii) antioxidant activity increase with the degree of polymerization for the compounds with (-)-epicatechin (epi) as structural unit (epi, dimer B2 (epi-epi) and trimer C1 (epi-epi-epi)); (iii) galloylation increases antioxidant activity of procyanidins, specially in the case of B2-3''-O-gallate dimer, which revealed the maximal trapping efficiency.